The Effectiveness of E-Court Implementation in the Resolution of Civil Cases in Indonesia - Aulya Brillianty Hennizar; Rasya Tuah Raditya; Ilham Ramadani; Sri Handayani (Jurnal Restorasi : Hukum dan Politik, 2026)
This study aims to analyze the effectiveness of the implementation of the e-Court system in the resolution of civil cases in Indonesia, particularly after the enactment of Supreme Court Regulation Number 1 of 2019 and its amendment in Supreme Court Regulation Number 7 of 2022. This research employs an empirical legal method with a qualitative approach, examining the conformity between normative provisions and practices in the field. Data were collected through interviews, observations, and documentation studies at the Palembang District Court, and were supported by secondary legal materials in the form of legislation, books, and scientific journals. The results show that the implementation of e-Court has had a positive impact in improving efficiency, transparency, and accessibility of judicial services, particularly in case administration processes such as registration, payment, and electronic document exchange. However, its effectiveness still faces several challenges, including limited technological infrastructure, low digital literacy among some users, and resistance to electronic court proceedings. Therefore, strengthening infrastructure, enhancing human resource capacity, and conducting continuous public outreach are necessary to ensure that the e-Court system can function optimally in realizing a simple, fast, and low-cost judiciary in Indonesia.